2023
DOI: 10.3389/fphys.2023.1180980
|View full text |Cite
|
Sign up to set email alerts
|

Satellite cell contribution to disease pathology in Duchenne muscular dystrophy

Abstract: Progressive muscle weakness and degeneration characterize Duchenne muscular dystrophy (DMD), a lethal, x-linked neuromuscular disorder that affects 1 in 5,000 boys. Loss of dystrophin protein leads to recurrent muscle degeneration, progressive fibrosis, chronic inflammation, and dysfunction of skeletal muscle resident stem cells, called satellite cells. Unfortunately, there is currently no cure for DMD. In this mini review, we discuss how satellite cells in dystrophic muscle are functionally impaired, and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 123 publications
0
5
0
Order By: Relevance
“…In the orderly progression through myogenesis, myogenic progenitors differentiate to acquire mature myocyte features that ultimately become multi-nucleated myofibers, a process that is shared during embryonic development and adult tissue remodeling [19,48,49]. In disease conditions such as DMD, satellite cell functions display significant alternations in polarity and asymmetric division, leading to the accumulation of a stem cell pool while attenuating myogenic progenitor commitment [50][51][52]. Various key aspects of stem cell dysfunction, involving reduced mitochondrial capacity, reactive oxygen species stress, senescence, altered plasticity, and aberrant epigenetic regulation in DMD, may collectively contribute to the defect of myogenic progenitors at mounting effective muscle regeneration in DMD [52].…”
Section: Circadian Clock In Muscle Stem Cell Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…In the orderly progression through myogenesis, myogenic progenitors differentiate to acquire mature myocyte features that ultimately become multi-nucleated myofibers, a process that is shared during embryonic development and adult tissue remodeling [19,48,49]. In disease conditions such as DMD, satellite cell functions display significant alternations in polarity and asymmetric division, leading to the accumulation of a stem cell pool while attenuating myogenic progenitor commitment [50][51][52]. Various key aspects of stem cell dysfunction, involving reduced mitochondrial capacity, reactive oxygen species stress, senescence, altered plasticity, and aberrant epigenetic regulation in DMD, may collectively contribute to the defect of myogenic progenitors at mounting effective muscle regeneration in DMD [52].…”
Section: Circadian Clock In Muscle Stem Cell Biologymentioning
confidence: 99%
“…In disease conditions such as DMD, satellite cell functions display significant alternations in polarity and asymmetric division, leading to the accumulation of a stem cell pool while attenuating myogenic progenitor commitment [50][51][52]. Various key aspects of stem cell dysfunction, involving reduced mitochondrial capacity, reactive oxygen species stress, senescence, altered plasticity, and aberrant epigenetic regulation in DMD, may collectively contribute to the defect of myogenic progenitors at mounting effective muscle regeneration in DMD [52]. Dissection of MuSC regulation by the circadian clock provides yet another layer to our current understanding of satellite cell dysfunctions involved in muscular dystrophies (Figure 2).…”
Section: Circadian Clock In Muscle Stem Cell Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Still, this hypothesis remains to be fully elucidated (Figure 2). Although a consensus has emerged over the years to enhance the functions of SCs and stimulate regeneration in dystrophy to improve the dystrophic phenotype, recent evidence has shown that slowing down the degeneration-regeneration cycles may also help to preserve skeletal muscle in dystrophies [4,126,151,[159][160][161][162][163][164]. Despite this debate, the scientific community agrees that skeletal muscle must be preserved by correcting the genetic defect of DMD.…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%
“…On the other hand, the well-being of skeletal muscle also depends on the ability to repair and regenerate new muscle fibers after traumatic events, thanks to the presence of adult stem cells, the satellite cells (SCs), first identified by Alexander Mauro [ 3 ]. SCs have two essential functions: (i) the ability to self-renew, which is essential to maintain and replenish the stem cell pool, and (ii) the capacity to differentiate into myogenic progenitor cells [ 4 ]. Defects in self-renewal ability result in a depleted SCs pool, impairing muscle regeneration capacity.…”
Section: Introductionmentioning
confidence: 99%